Effect of metribuzin on nitrogen metabolism and iron acquisition in Zea mays. Issue 8 (14th September 2019) - Bartucca, Maria Luce; Mimmo, Tanja; Cesco, Stefano; Panfili, Ivan; Del Buono, Daniele
ABSTRACT: Weed control based on herbicides is essential to guarantee high levels of crop productivity. However, these compounds can affect ecosystems and non-target crops. Therefore, a research was carried out in order to investigate the effect of metribuzin (ME) on the capacity of Zea mays L. (maize) to acquire iron (Fe). ME reduced the chlorophyll content, the concentration of phytosiderophores (PSs) released by roots and their Fe content. Both the shoots and roots of ME-treated plants showed increases in ammonia ( NH 4 + ) concentrations. This effect was ascribed to the decreases in the activity of glutamine synthetase (GS; EC 6.3.1.2) and glutamine amide-2-oxoglutarate aminotransferase (GOGAT; EC 1.4.1.14). The results indicate that the interference exerted by ME on nitrogen organication was the cause of the drop in the PSs release and of the reduction in the Fe content.